2017
DOI: 10.1302/1863-2548.11.170078
|View full text |Cite
|
Sign up to set email alerts
|

Avascular necrosis in children with cerebral palsy after reconstructive hip surgery

Abstract: PurposeProgressive hip displacement is one of the most common orthopaedic pathologies in children with cerebral palsy (CP). Reconstructive hip surgery has become the standard treatment of care. Reported avascular necrosis (AVN) rates for hip reconstructive surgery in these patients vary widely in the literature. The purpose of this study is to identify the frequency and associated risk factors of AVN for reconstructive hip procedures.MethodsA retrospective analysis was performed of 70 cases of reconstructive h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 46 publications
1
21
1
Order By: Relevance
“…However, they were unable to identify any associations between potential risk factors, such as age, preoperative Reimer's MP, or length of follow-up. They noted, however, that this could be due to the poor quality of the included studies and the general lack of demographic data [12]. Two included studies in the Hesketh et al review provided conflicting results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they were unable to identify any associations between potential risk factors, such as age, preoperative Reimer's MP, or length of follow-up. They noted, however, that this could be due to the poor quality of the included studies and the general lack of demographic data [12]. Two included studies in the Hesketh et al review provided conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of AVN after hip procedures for the treatment of developmental dysplasia of the hip is well studied in the literature with little research investigating procedures in children with CP. The true incidence after hip reconstruction in CP patients is difficult to ascertain as the rate reported in the literature varies greatly, between 0 and 69% [12,16]. The subjective nature of radiographic interpretation undoubtedly plays a large role in this variance.…”
Section: Introductionmentioning
confidence: 99%
“…However, many have failed to explain their methodology for diagnosing AVN 8 , 25 27 . Furthermore, whilst those that have, simply adopted different AVN classification systems for DDH 5 7 , 9 . There are several classification systems used to assess AVN following the treatment of DDH 1 , 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, very few have investigated the relationship between remodelling and AVN, making it difficult to determine its influence on outcomes. Exacerbating this, in a recent study investigating remodelling, the authors simply stated the incidence without outlining any clear methodology of recognition 7 . Rutz et al 14 reported that 6.6% of their hips demonstrated early radiographic progression of a femoral head deformity and subsequent delayed remodelling that took up to 2 years to complete.…”
Section: Discussionmentioning
confidence: 99%
“…Complications and reoperations are relatively common in acetabuloplasty procedures for patient with CP [ 3 , 21 , 22 , 32 34 ]. McNerney et al reported an 8% incidence of AVN in their study [ 3 ], with an even higher incidence in patients with open triradiate cartilage (68.7%) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%